Migration practice as creative practice : an interdisciplinary exploration of migration - Hack-Polay, Dieu; Mahmoud, Ali B; Rydzik, Agnieszka; Rahman, Mahfuzur; Igwe, Paul Agu; Bosworth, Gary (Emerald Publishing, 2021)
Migration Practice as Creative Practicepresents an in-depth evaluation of the contributions made by migrants to modern socio-economic structures. The book also discusses the creative energies that migrant inject in the economic structures in both private and public spheres.